The dynamic pattern of recurrence in curatively resected non-small cell lung cancer patients: experiences at a single institution - Yamauchi, Yoshikane; Muley, Thomas; Safi, Seyer; Rieken, Stefan; Bischoff, Helge; Kappes, Jutta; Warth, Arne; Herth, Felix; Dienemann, Hendrik; Hoffmann, Hans (Lung cancer, 2015)
Purpose - To investigate the hazard function of tumor recurrence in patients with completely (R0) resected non-small cell lung cancer. - Methods - A total of 1374 patients treated between 2003 and 2009 with complete resection and systematic lymph node dissection were studied. The risk of recurrence at a given time after operation was studied utilizing the cause-specific hazard function. Recurrence was categorized as local recurrence or distant recurrence. The risk distribution was assessed using clinical and pathological factors. - Results - The hazard function for recurrence presented an early peak at approximately 10 months after surgery and maintained a tapered plateau-like tail extending up to 8 years. A similar risk pattern was detected for both local recurrence and distant recurrence, while the risk of distant recurrence was higher than that of local recurrence. The double-peaked pattern of hazard rate was present in several subgroups, such as p-stage IA patients. A comparison of histology and status of nodal involvement showed that pN1-2 adenocarcinoma patients demonstrated a high hazard rate of distant recurrence and that pN0 adenocarcinoma patients exhibited a small recurrent risk for a longer time. Squamous cell carcinoma patients showed only little difference in risk. - Conclusions - The data may be useful to select patients at high risk of recurrence and may provide information for each patient to decide how to manage the postoperative follow-up individually.